The impact of interior layout of designer's office on employee's performance at shop office in Kuala Lumpur - Arita Hanim binti Awang (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2018)
Kuala Lumpur as the capital city of Malaysia is booming with development of new commercial buildings. The major components of commercial floor space in Kuala Lumpur are offices, shopping, hotels and service apartments and other services. Office is still the highest services targeted to the strategic zone in Kuala Lumpur and its conurbation. Among the types of office building in Malaysia, shop offices stayed dominant demand for small and medium (SME) business activities. A small office space with a large number of employees and many space requirements is the major problem faced by small private organizations in Malaysia. As the cost of rental are now rising, efficient planning and utilization of the office space is becoming crucial. Mostly the office is designed with due importance to the nature of the job and the individuals that are working in that office. Therefore, designer's office which located in shop office building typology is selected as the office setting for this study. The aim of the research is to examine the relationship between offices interior layout and environment in shop office typology and developed a framework of best practice criteria for designer's office in shop offices typology. The objectives of the study firstly 1) to evaluate the existing condition of interior design and layout of designer's office at shop offices typology secondly 2) To obtain employees' perception towards the existing office condition and its relationship towards their productivities and performance thirdly 3) To identify the impact of building typology towards interior layout in shop office building typology and 4) to test the office environmental factor in a controlled subjective experiment in order to understand their influence towards employees task performance and perceived satisfaction and the final objectives is 5) To underline the criteria for best practice of designer's office setting in shop office building typology. This research comprises of three distinct stages of methodology which are 1) Case Study which consist of field observations and field survey of 17 Designer's Offices in Kuala Lumpur, 2) Computer Simulation of Space Syntax Analysis and 3) Control Subjective Experiment of focus group consisting 8 interior designers as respondents. Duffy's concept of office layout which is, DEN, HIVE, CLUB and CELL types of layout concept has been selected as the basis for office layout analysis throughout the study. Findings from the case study suggest that Majority of Designer's office uses DEN type of layout concept. Meanwhile the most preferable layout in the control subjective experiments is HIVE type over the DEN type. Space syntax analysis on building typology suggest that shop office type with high Connectivity Value gives more flexibility to accommodate DEN and HIVE types of layout. The research showed that office layout and design has significant impact towards employees' performance of Designer's Office in Malaysia's shop offices typology.